Serum progranulin levels in axial spondyloarthropathy and relationship with clinical features - Didem İldemir Doğangün,; Meliha Kasapoğlu Aksoy,; Lale Altan, (Archives of Rheumatology, 2022)
Objectives: In this study, we aimed to investigate the serum progranulin (PGRN) levels in patients with axial spondyloarthropathy (AxSpA) and to identify the correlation between disease activity, symptom severity, acute phase reactant (APR), and serum PGNR levels in patients with AxSpA. Patients and methods: This prospective, cross-sectional study included a total of 152 patients (105 males, 47 females; mean age: 41.8±10.3; range 20 to 65 years) with AxSpA according to the 2009 Assessment of SpondyloArthritis Society (ASAS) criteria who received treatment and 100 healthy individuals (61 males, 39 females; mean age 43.4±14.2; range 20 to 65 years) between February 2018 and February 2019. Serum PGRN levels from the venous blood were analyzed in both groups. The clinical AxSpA assessment scales were used in the patient group. Erythrocyte sedimentation rate and C-reactive protein levels were examined. Results: The mean serum PGRN level was 6.9±5.4 ng/mL in the patient group and 11.2±6.0 ng/mL in the control group. Serum PGRN level was significantly higher in the control group (p<0.001). No significant correlation was found between the PGRN levels and disease activity, symptom severity, duration of disease, and age of the patient (p>>0.05). Serum PGRN levels were significantly higher in female patients in the patient group (p<0.01). In the control group, the serum PGRN levels of individuals with a high body mass index were significantly higher (p=0.001). Conclusion: Serum PGRN levels of patients with AxSpA who are under treatment and follow-up are significantly lower than healthy individuals. Serum PGRN levels in female patients with AxSpA are also significantly higher than male patients. Serum PGRN levels do not seem to be related to disease activity.